PELATIHAN HATHA YOGA BAGI DOSEN DAN PEGAWAI DI UNIVERSITAS NGURAH RAI DENPASAR - Dwidyaniti Wira, Ida Ayu (Institut Hindu Dharma Negeri Denpasar, 2020)
Hinduism has many teachings related to ethics, morals and health, one of which is the teachings of Hatha yoga. In this case the Hatha Yoga training is considered very important in efforts to improve ethics, morals and public health, especially for lecturers and staff at Ngurah Rai University, Denpasar. This research is in the form of a qualitative design. Data were collected using observation techniques, interview techniques and literature techniques. After the data is collected, the data are analyzed by descriptive qualitative and interpretative descriptive methods. Based on this analysis, conclusions are obtained as a result of the study, as follows: (1) The process of implementing the Hatha Yoga training consists of opening greetings and joint prayers, pranayama exercises, motion warm-ups, Surya Namaskara motion exercises, loose asanas exercises, Savasana, Meditation and Hasya Yoga (Closing). (2) The benefits of Hatha Yoga training are to improve physical, mental and spiritual health.